THE EVALUATION OF TAX PLANNING ON INCOME TAX ARTICLE 21 BY USING GROSS-UP METHOD IN FORM OF CORPORATE TAX SAVINGS (STUDY AT PT. PG KEBON AGUNG MALANG PERIOD OF 2009-2012) - Saputro, Januar Cahyo (Jurnal Mahasiswa Perpajakan, 2014)
This research is aimed to evaluate tax planning on income tax article 21 by using gross up method that done by PT. PG Kebon Agung in period of 2009-2012 in order to achieve corporate tax savings. This research used descriptive research with case study approach by using quantitative data. This research used a secondary data which is collected from corporate’s profile, corporate policy related employee benefit, income statement and fiscal reconciliation. All of information that can support this research which is taken by documentation method. The result of this research are: (1) Tax Planning that done by PT PG Kebon Agung has been treat by using gross up in properly correct based on rules and regulation so that corporate allocate tax allowance cost as form tax planning cost in the amount of IDR 275.796.836 or 1,23% during 2009-2012 efficiently and effectively  and it can minimize corporate tax payable in form of corporate tax savings in the amount of IDR 781.996.470 or 2,807% during 2009-2012 effectively. (2) The feasibility of tax planning program is also shows positive coefficient which is NPV > 0 amounted to IDR  1.809.624.700 and PVI > 1 which is amounted to number  2,62. It means that tax planning program that done by  program PT PG Kebon Agung is feasible to do. Keywords: Tax Planning, Income Tax article 21, Gross up Method, Evaluation